1997
DOI: 10.1080/10683169708410822
|View full text |Cite
|
Sign up to set email alerts
|

Is overpunishment fairer than underpunishment? Perceptions of deviations from equity

Abstract: Thrce studies are presented which test hypothtscs derived from Equity Theory, Prospect Theory and the principle of Diminishing Marginal Value with regard to preferences for overpunishment and underpunishment in the assignment of penalties to offences of varying severity. The f i t two studies showed that, with dimerent subject sarnpl~s offenas, and kinds of punishments subjects indicated a marked preference for overpunishment rather than underpunishment. when both over punishment and underpunishment deviated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It would be unfair to impose upon the transgressor either too weak (i.e., under-punishment) or too strong punishment (i.e., over-punishment), compared to the severity of their norm violation. A Human-Human Interaction (HHI) study (Wagstaff and Preece 1997) showed that, when forced to choose between under-and over-punishment that equally deviated from the fitting punishment, people's endorsement of over-and under-punishment was similar for mild violations but their endorsement of over-punishment was stronger for severe violations. Thus, the impact of over-and underpunishment on people's perception of fairness may also be influenced by various factors like the severity of a norm violation.…”
Section: Fairness Of Punishmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be unfair to impose upon the transgressor either too weak (i.e., under-punishment) or too strong punishment (i.e., over-punishment), compared to the severity of their norm violation. A Human-Human Interaction (HHI) study (Wagstaff and Preece 1997) showed that, when forced to choose between under-and over-punishment that equally deviated from the fitting punishment, people's endorsement of over-and under-punishment was similar for mild violations but their endorsement of over-punishment was stronger for severe violations. Thus, the impact of over-and underpunishment on people's perception of fairness may also be influenced by various factors like the severity of a norm violation.…”
Section: Fairness Of Punishmentmentioning
confidence: 99%
“…Next, based upon the findings from human-human interactions (Wagstaff and Preece 1997), we present our hypotheses about the perceived fairness of over-punishment and under-punishment as a function of the severity of a norm violation.…”
Section: Working Hypothesesmentioning
confidence: 99%